From time-out to expulsion: A national review of states' center-based child care licensing exclusionary discipline regulations. (October 2022) - Buell, Martha; Fidel, Rachel; Hustedt, Jason T.; Kuntz, Stephanie; Slicker, Gerilyn
Highlights: There is considerable regulatory variation in exclusionary discipline terminology. Within-program regulatory language includes time-out, isolation, and confinement. Out-of-program regulations - suspensions and expulsions often lack specifics. Vague regulatory language allows for imprecise policy development and implementation. Abstract: State-level child care licensing regulations dictate required policy elements and allowable disciplinary options available to programs, with permitted exclusionary discipline strategies ranging from a brief time-out to expulsion. This national review presents a qualitative content analysis of exclusionary discipline regulations within state-level, center-based child care licensing policies. As exclusionary discipline is disproportionally applied to boys, children of color, and children with disabilities, examining what is and is not allowed in terms of exclusionary discipline is important to ensure equity and access. The findings include an overview of the allowed versus prohibited exclusion practices, and within-program versus out-of-program exclusions, including expulsions, as well as details regarding specificity in required policy and practice at the program level. The findings are discussed in terms of implications for policymakers, researchers, and practitioners.